2021
DOI: 10.1098/rsta.2020.0202
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of synergistic image registration for motion-corrected coronary NaF-PET-MR

Abstract: Coronary artery disease (CAD) is caused by the formation of plaques in the coronary arteries and is one of the most common cardiovascular diseases. NaF-PET can be used to assess plaque composition, which could be important for therapy planning. One of the main challenges of NaF-PET is cardiac and respiratory motion which can strongly impair diagnostic accuracy. In this study, we investigated the use of a synergistic image registration approach which combined motion-resolved MR and PET data to estimate cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Finally, this work opens the door for future research, for example by using the motion blurring information from PET as a quality assurance for motion compensation in MR. This concept appears possible considering that a recent study combined both, the motion information from both modalities which improved final motion model accuracy by 15% ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this work opens the door for future research, for example by using the motion blurring information from PET as a quality assurance for motion compensation in MR. This concept appears possible considering that a recent study combined both, the motion information from both modalities which improved final motion model accuracy by 15% ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another challenging area to apply motion correction is in the coronary arteries as in the paradigm illustrated via a computational simulation study by Petibon et al [83]. The advantages of the synergistic use of PET-MRI for respiratory and cardiac motion correction have been visible in recent clinical studies where it was shown that the visualization of uptake in coronary plaques can be improved [39].…”
Section: (C) Cardiovascular Imagingmentioning
confidence: 99%
“…Finally, a synergistic approach has recently been implemented by Mayer et al where they used mutual information from PET and MRI to both derive the motion vectors and correct for motion [ 39 ].…”
Section: Motion Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mayer et al show that using images from both modalities for motion estimation through synergistic PET-MRI image registration allows for more accurate cardiac and respiratory motion estimation. This can improve the quality of [ 18 F]NaF PET images of coronary plaques [ 9 ].…”
Section: Contributions In This Issuementioning
confidence: 99%